The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep31179
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral blood minimum residual disease at day 8 of induction therapy in high-risk pediatric patients with acute lymphocytic leukemia

Abstract: Risk stratification and treatment intensification, based on minimal residual disease (MRD) mensurement, changed the prognosis of pediatric patients with acute lymphocytic leukemia (ALL). The main aim of this study was to investigate whether peripheral blood (PB) MRD measurement at day 8 (D8) could predict the risk stratification category determined by bone marrow (BM) MRD at day 15 (D15). The study was performed prospectively, in a cohort of 40 children with B-lineage ALL, adopting the protocol of the Brazilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Thus, currently, BM is preferred over PB for MRD assessment. However, detection of PB MRD has been shown to predict the risk stratification category determined by BM MRD (Salina et al, 2016;Volejnikova et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, currently, BM is preferred over PB for MRD assessment. However, detection of PB MRD has been shown to predict the risk stratification category determined by BM MRD (Salina et al, 2016;Volejnikova et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, multiparametric flow cytometry (MFC) has become a powerful tool in MRD detection. Although bone marrow (BM) is generally the preferred specimen type for MFC MRD assessment because of its higher sensitivity, the utility of peripheral blood (PB) MRD assessment is also being explored due to the ease of sample collection that allows for frequent sampling (Salina et al, 2016; Volejnikova et al, 2011). It may also add clinical and diagnostic value in early detection of relapsed extramedullary disease (Keegan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood MRD ,1% by day 8 has been used as one of the prognostic factors in pediatric ALL studies. 26,27 Our study used both bortezomib and rituximab during induction, using the drug synergy in the initial phase of therapy to achieve early and deep responses. This end point was used as an indicator of the in vivo activity of this combination in the first 7 days of induction, as no drug other than prednisolone was administered during this period.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated the role of peripheral blood MRD at day 8 of the induction therapy. 28 The MRD measurement by the MFC is a feasible approach in our routine practice to refine the risk stratification of our patients. Our data suggest that the MRD at D15 has an influence on risk classification, being particularly useful for stratification of patients with a more favorable prognosis, as demonstrated in the literature.…”
Section: Discussionmentioning
confidence: 99%